Dywersyfikacja narzędzi informatycznych wspomagających zarządzanie łańcuchem dostaw - Owoc, Mieczysław L.; Wilk, Krzysztof (Information Technology Tools Diversity Supporting the Supply Chain Management, 2009)
There are many information technology tools helping logistics management e.g. SCM (Supply Chain Management). Some of them support particular stages of logistics management and some of them aim at assisting the whole process. The purpose of this article is to identify and analyze the existing IT tools in logistics with a suggestion of their classification. We take into consideration the following criteria: the extend of process support, used methods of process service or the universality of the solutions. After introduction including problem and used methods presentations the supply chain management are characterized with its stages and kinds of information processes implemented in management. Then, the proposition of the criteria differentiating the IT tools used in supply chain management and the taxonomy of programmes helping these processes are described. The article ends with conclusions concerning the future tendencies of developing further IT tools in logistics. The role of Artificial Intelligence in IT tools for supply chain management solutions based on previous products as one of more promising future solutions is stressed. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 240-250